Assessing students' multimodal compositions: an analysis of the literature. Issue 3 (14th October 2019) - Anderson, Kate T.; Kachorsky, Dani
Abstract : Purpose: This article presents an analysis of empirical literature on classroom assessment of students' multimodal compositions to characterize the field and make recommendations for teachers and researchers. Design/methodology/approach: An interpretive synthesis of the literature related to practices and possibilities for assessing students' multimodal compositions. Findings: Findings present three overarching types of studies across the body of literature on assessment of student multimodal compositions: reshaping educational practices, promoting multiliteracies approaches to learning and evaluating students' understanding and competence. These studies' recommendations range along a continuum of more to less structural changes to "what counts" in classrooms. Research limitations/implications: This review only considers studies published in English from 2000to 2019. Future studies could extend these parameters. Practical implications: This analysis of the literature on assessing student multimodal compositions highlights foundational differences across studies' purposes and offers guidance for educations seeking to revise their practices, whether their goals are more theoretical/philosophical, oriented toward reshaping classroom practice or focused on ways of measuring student understanding. Social implications: Rethinking assessment can reshape educational practices to be more equitable, more theoretically commensurate with teachers' beliefs and/or include more thorough and accurate measures of student understanding. Changes to any or all of these facets of educational practices can lead to continued discussion and change regarding the role of multimodal composition in teaching and learning. Originality/value: This study fills a gap in the literature by considering what empirical studies suggest about why, how and what to assess with regard to multimodal compositions.